Modified hollow titanium oxide as well as preparation method and application thereof

Through the preparation method of modified hollow titanium oxide, the existing titanium oxide powder has been solved, and the effect of high concealing performance and good dispersion is achieved, and it is suitable for cosmetic powders.

CN119684823APending Publication Date: 2025-03-25SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411627686.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When used in cosmetics, existing titanium oxide powders have poor dispersion and stability, resulting in poor concealing performance and affecting the skin feeling.

Method used

Using the preparation method of modified hollow titanium oxide, nanocarbon powder is used as a template, combined with hydroxypropyl cellulose and tetrabutyl titanate, and then dried and sintered to obtain hollow titanium oxide powder, and surface modification is performed by modified hydroxyfluorosilicone oil.

Benefits of technology

It improves the concealing performance and dispersion of titanium oxide powder, reduces the density of titanium oxide, improves the use efficiency of powder, and is suitable for cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684823A_ABST
    Figure CN119684823A_ABST
Patent Text Reader

Abstract

The invention discloses modified hollow titanium oxide as well as a preparation method and application thereof. The preparation method comprises the following steps: preparing a mixed solution containing nano carbon powder, hydroxy propyl cellulose and tetrabutyl titanate; adding an ethanol water solution, stirring at 0-5 DEG C, heating to 70-90 DEG C, and stirring to obtain a carbon-titanium oxide powder dispersion liquid; drying and sintering to remove a carbon core to obtain hollow titanium oxide powder; and reacting the hollow titanium oxide powder with the modified hydroxyl fluorosilicone oil and a catalyst in a solvent to obtain the modified hollow titanium oxide. The particle size of the modified hollow titanium oxide provided by the invention can enable incident light to be scattered for multiple times in a hollow nanostructure, and compared with existing commercial concealing titanium oxide powder with a solid structure, the concealing performance is improved, and meanwhile, the hollow structure can reduce the density of titanium oxide and improve the use efficiency of the powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium oxide, and in particular to a modified hollow titanium oxide and a preparation method and application thereof. Background Art

[0002] Foundation makeup products such as foundation cream, liquid foundation and BB cream contain powdery raw materials. After being applied to the skin surface, they can form a covering layer on the skin surface, cover facial blemishes and correct facial skin color. At the same time, some powdery raw materials also have the functions of smoothness, absorbing sebum and sweat, etc.

[0003] The powdery raw materials in cosmetics are generally natural mineral powders, and commonly used ones are titanium dioxide (also known as "titanium dioxide"), zinc oxide (also known as "zinc white"), talc, kaolin, bentonite, etc. Among them, titanium dioxide is the whitest in color, has a large refractive index, strong covering power, and is the most widely used, but its dispersibility is poor, resulting in powder shedding and sticking when a large amount is added. At present, commercial titanium oxide for concealing blemishes is solid titanium oxide powder (particle size ~ 200nm). In order to achieve high concealing performance, more titanium oxide powder needs to be added, but adding too much powder often leads to poor dispersion stability and affects skin feel. Therefore, it is of practical significance to prepare powders with higher scattering and high dispersion properties.

[0004] In order to improve the powder's light scattering performance and blemish-covering performance, the center of the titanium oxide powder is designed to be a hollow structure. The hollow structure allows the incident light to be scattered multiple times in the hollow nanostructure, which is beneficial to improving the scattering performance. At the same time, the hollow structure can reduce the packing density of titanium oxide and improve the use efficiency of the powder.

[0005] At present, the preparation methods of hollow titanium oxide can be divided into three types according to the different templates used: hard template method, soft template method and self-template method. Among them, the most common method is hard template, which means that the target material is coated on the outside of the rigid template to form a shell, and then the template is removed by various methods to obtain a hollow structure. In the process of synthesizing hollow materials by hard template method, in order to achieve better coating of the material on the template surface, it is often necessary to modify the template surface, such as changing the polarity and electronegativity of the surface. Some common hard templates, such as metal particles, polymer beads (such as polystyrene PS, phenolic resin, polymethyl methacrylate PMMA, melamine resin MF, etc.), silica and carbon spheres, can be removed by simple calcination, acid washing, alkali washing and other processes. The size of the cavity can be adjusted by the template, and the thickness of the shell can be determined by the preparation process of the coating material.

[0006] For example, Chinese patent CN105406041B provides a hollow titanium oxide composite material, preparation method and application, wherein a phenolic resin layer as a sacrificial template is coated on the surface of the active material, and then a porous titanium oxide material is coated, and the template is removed and CaH2 After treatment, a composite material containing hollow titanium oxide and active materials with abundant oxygen vacancies is obtained. This method requires the use of CaH 2 The processing is complicated, and it is coated with a variety of heavy metal ions such as cobalt, manganese, and nickel, and cannot be used in the cosmetics field. Chinese patent CN113488651B discloses a titanium oxide @ C hollow composite skeleton embedded with precious metal silver, and its preparation method and application. The SiO2@Ag composite template uniformly loaded with silver nanoparticles is prepared by using a silica template, and a titanium source is added for hydrolysis to obtain a titanium oxide precursor on the outer layer of the composite template, followed by in-situ polymerization to obtain a nitrogen-doped carbon-coated composite skeleton precursor, and finally calcined at a certain temperature, and the silica template is etched with a strong alkali to obtain a titanium oxide @ C hollow composite skeleton embedded with precious metal silver. The composite hollow skeleton material has a closed cavity structure, good conductivity and excellent gradient lithium affinity as a battery negative electrode material, and is not suitable as a cosmetic powder. Chinese patent CN101279233A discloses a hollow titanium oxide dark electrophoretic particle for electrophoretic display and its preparation method, using acrylic polymer or styrene polymer microspheres as seeds, the outer layer is coated with titanium oxide hydrate, and finally dried and calcined to prepare the corresponding polymer / silicon dioxide microspheres. Then, after high-temperature calcination in ammonia, hydrogen or Ar gas, microspheres with hollow structures and different colors are obtained. This preparation method is relatively complicated, requiring the preparation of templates and a complex firing process, and the obtained hollow titanium oxide is severely agglomerated, and the wall thickness is too thin, resulting in poor concealment. Summary of the invention

[0007] In view of the above technical problems, the present invention provides a modified hollow titanium oxide and a preparation method and application thereof. The preparation method of the modified hollow titanium oxide is simple and can be used for cosmetic powders.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] In one aspect, the present invention provides a method for preparing a modified hollow titanium oxide, comprising the following steps:

[0010] (1) preparing a mixed solution containing nano carbon powder, hydroxypropyl cellulose and tetrabutyl titanate;

[0011] (2) adding ethanol aqueous solution, stirring at 0-5° C., and then heating to 70-90° C. and stirring to obtain a carbon-titanium oxide powder dispersion;

[0012] (3) drying and sintering to remove the carbon core to obtain hollow titanium oxide powder;

[0013] (4) reacting the hollow titanium oxide powder obtained in step (3) with modified hydroxy fluorosilicone oil and a catalyst in a solvent to obtain the modified hollow titanium oxide.

[0014] As a preferred embodiment, in step (1), the solvent of the mixed solution is ethanol;

[0015] Preferably, the particle size of the nano carbon powder is 100 to 200 nm;

[0016] Preferably, the mass ratio of the nano carbon powder: ethanol: hydroxypropyl cellulose: tetrabutyl titanate is 1: 5000-50000: 4-100: 500-5000;

[0017] In some specific embodiments, the preparation process of the mixed solution is: adding nano carbon powder to a solvent and dispersing it ultrasonically; adding hydroxypropyl cellulose to dissolve it; adding tetrabutyl titanate while stirring at 0-5°C and stirring evenly.

[0018] As a preferred embodiment, in step (2), the stirring time at 0 to 5° C. is 1.5 to 3 h;

[0019] Preferably, the stirring time at 70-90° C. is 4-5 h;

[0020] In certain specific embodiments, the mass fraction of ethanol in the ethanol aqueous solution is 80% to 95%.

[0021] As a preferred embodiment, in step (3), the sintering temperature is 700-800° C., and the sintering time is 1-4 hours;

[0022] Preferably, the drying is spray drying.

[0023] As a preferred embodiment, in step (4), the reaction is stirred and refluxed at 70-80°C for 3-6 hours, and then stirred and reacted at 90-120°C for 3-6 hours;

[0024] Preferably, the solvent is ethanol;

[0025] Preferably, the catalyst is tetrabutyl titanate, and the mass ratio of the catalyst to the hollow titanium oxide powder is 0.05 to 0.2:1.

[0026] Preferably, the mass ratio of the modified hydroxy fluorosilicone oil to the hollow titanium oxide powder is 5 to 20:100.

[0027] As a preferred embodiment, in step (4), the modified hydroxy fluorosilicone oil is hydroxy fluorosilicone oil modified by a silane coupling agent;

[0028] Preferably, the preparation method of the modified hydroxy fluorosilicone oil comprises the following steps: heating the hydroxy fluorosilicone oil, a silane coupling agent and an organic tin catalyst at 80 to 100° C. for 4 to 8 hours to obtain the modified hydroxy fluorosilicone oil;

[0029] In certain specific embodiments, the organotin catalyst is dibutyltin dilaurate;

[0030] Preferably, the silane coupling agent is selected from at least one of octyltrimethoxysilane, methyltrimethoxysilane, octyltriethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane and dimethyldiethoxysilane;

[0031] Preferably, the mass ratio of the hydroxyfluorosilicone oil to the organotin catalyst is 1.5-2.5:0.15-0.25.

[0032] Preferably, the mass ratio of the hydroxyfluorosilicone oil to the silane coupling agent is 5-20:0.1-5.

[0033] In another aspect, the present invention provides modified hollow titanium oxide obtained by the above preparation method.

[0034] In another aspect, the present invention provides use of the modified hollow titanium oxide in preparing cosmetics.

[0035] The above technical solution has the following advantages or beneficial effects:

[0036] (1) The raw materials for preparing the modified hollow titanium oxide provided by the present invention are non-toxic and harmless and are all included in the catalog of cosmetic raw materials. The commercial nano-carbon powder is used as the template raw material. The preparation process is simple and feasible, green and environmentally friendly, and is suitable for the field of daily chemical products such as cosmetics.

[0037] (2) The modified hollow titanium oxide provided by the present invention has a particle size of 100 to 300 nm and a hollow structure, which allows the incident light to be scattered multiple times in the hollow nanostructure. Compared with the existing commercial blemish-covering titanium oxide powder with a solid structure, the blemish-covering performance is improved. At the same time, the hollow structure can reduce the density of titanium oxide and improve the use efficiency of the powder.

[0038] (3) The present invention uses non-toxic, physiologically inert modified hydroxyl fluorosilicone oil to modify the surface of hollow titanium oxide, and the dispersion performance of the powder modified with organosilicon in organic solvents is significantly improved, thereby expanding the application range of the powder. Experiments show that the modified hollow titanium oxide prepared by the present invention is dispersed in phenyl polydimethylsiloxane, and only a small amount of sedimentation occurs after standing for 24 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a transmission electron microscope image of the modified hollow titanium oxide prepared in Example 1 of the present invention;

[0040] Figure 2 This is a scanning electron microscope image of the modified hollow titanium oxide prepared in Example 1 of the present invention;

[0041] Figure 3This is a comparison chart of the dispersibility of the hollow titanium oxide prepared in Comparative Example 1 of the present invention and the modified hollow titanium oxide prepared in Example 1. DETAILED DESCRIPTION

[0042] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0043] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0044] In the following examples and comparative examples:

[0045] Hydroxyfluorosilicone oil was purchased from Guangzhou Jibisheng Technology Industry Co., Ltd., model number DFO-MF-X.

[0046] Embodiment 1:

[0047] (1) 0.05 g of nano-carbon powder with a particle size of 150 nm was added to 1000 g of ethanol and completely dispersed by ultrasonication; 0.2 g of hydroxypropyl cellulose was added and dissolved completely, and then stirred at 4° C. to cool, and then 80 g of tetrabutyl titanate was added and stirred to obtain a mixed solution;

[0048] (2) 40 g of water and 400 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 5 ° C for 2 h, and then heated to 80 ° C and stirred for 4 h to obtain a gray carbon-titanium oxide powder dispersion;

[0049] (3) spray drying the carbon-titanium oxide powder dispersion, collecting the dried powder, and sintering it at 700° C. for 4 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder;

[0050] (4) 10.0 g of hollow titanium oxide powder was added with 1.2 g of modified hydroxy fluorosilicone oil, 300 g of ethanol, and 0.1 g of tetrabutyl titanate. The mixture was stirred and refluxed at 80° C. for 4 h, and then stirred at 90° C. for 4 h to complete the reaction. At the same time, the excess solvent (ethanol) was removed to obtain a highly scattering and highly dispersible modified hollow titanium oxide.

[0051] The preparation process of modified hydroxy fluorosilicone oil is as follows: 1.5 g hydroxy fluorosilicone oil (purchased from Guangzhou Daxi Company, model DX-8011) is mixed with 0.25 g methyltrimethoxysilane, 0.2 g dibutyltin dilaurate is added, and the mixture is heated at 85°C for 5 hours to obtain modified hydroxy fluorosilicone oil.

[0052] Figure 1 and Figure 2 The transmission electron microscope image and scanning electron microscope image of the modified hollow titanium oxide prepared in Example 1 show that the particle size of the powder is 100 to 300 nm and has an obvious hollow structure.

[0053] Embodiment 2:

[0054] (1) 0.10 g of nano-carbon powder with a particle size of 200 nm was added to 1200 g of ethanol and completely dispersed by ultrasonication; 1.5 g of hydroxypropyl cellulose was added and dissolved completely, and then placed at 0° C. and stirred to cool, and then 100 g of tetrabutyl titanate was added and stirred to disperse to obtain a mixed solution;

[0055] (2) 50 g of water and 300 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 4 ° C for 2 h, and then heated to 70 ° C and stirred for 5 h to obtain a gray carbon-titanium oxide powder dispersion;

[0056] (3) spray drying the carbon-titanium oxide powder dispersion, collecting the dried powder, and sintering it at 800° C. for 2 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder;

[0057] (4) Take 10.0 g of hollow titanium oxide powder, add 2 g of modified hydroxy fluorosilicone oil, 800 g of ethanol, and 0.2 g of tetrabutyl titanate, stir and reflux at 80 ° C for 3 h, stir at 100 ° C for 3 h to complete the reaction, and remove excess solvent (ethanol) to obtain highly scattering and highly dispersible modified hollow titanium oxide;

[0058] The modified hydroxy fluorosilicone oil is prepared by the following process: 2.5 g of hydroxy fluorosilicone oil is mixed with 0.5 g of methyltrimethoxysilane, 0.15 g of dibutyltin dilaurate is added, and the mixture is heated at 90° C. for 6 h to obtain the modified hydroxy fluorosilicone oil.

[0059] The particle size of the modified hollow titanium oxide prepared in Example 2 is 200 to 300 nm.

[0060] Embodiment 3:

[0061] (1) 0.10 g of nano-carbon powder with a particle size of 100 nm was added to 1200 g of ethanol and completely dispersed by ultrasonication; 2.0 g of hydroxypropyl cellulose was added and dissolved completely, and then stirred and cooled at 3° C., and then 100 g of tetrabutyl titanate was added and stirred and dispersed to obtain a mixed solution;

[0062] (2) 50 g of water and 300 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 3 ° C for 2 h, and then heated to 70 ° C and stirred for 5 h to obtain a gray carbon-titanium oxide powder dispersion;

[0063] (3) spray drying the carbon-titanium oxide powder dispersion, collecting the dried powder, and then sintering it at 750° C. for 3 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder;

[0064] (4) Take 10.0 g of hollow titanium oxide powder, add 1.0 g of modified hydroxy fluorosilicone oil, 800 g of ethanol, and 0.05 g of tetrabutyl titanate, stir and reflux at 80° C. for 4 h, stir at 110° C. for 3 h in an open air until the reaction is complete, and remove excess solvent (ethanol) to obtain highly scattering and highly dispersible modified hollow titanium oxide;

[0065] The modified hydroxy fluorosilicone oil is prepared by the following process: 1.5 g of hydroxy fluorosilicone oil is mixed with 0.5 g of dimethyldimethoxysilane, 0.2 g of dibutyltin dilaurate is added, and the mixture is heated at 100° C. for 5 h to obtain the modified hydroxy fluorosilicone oil.

[0066] The particle size of the modified hollow titanium oxide prepared in Example 3 is 200-300 nm.

[0067] Embodiment 4:

[0068] (1) 0.10 g of nano-carbon powder with a particle size of 50 nm was added to 3000 g of ethanol and completely dispersed by ultrasonication; 3 g of hydroxypropyl cellulose was added and dissolved completely, and then stirred and cooled at 3° C., and then 100 g of tetrabutyl titanate was added and stirred and dispersed to obtain a mixed solution;

[0069] (2) 50 g of water and 300 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 3 ° C for 2 h, and then heated to 70 ° C and stirred for 5 h to obtain a gray carbon-titanium oxide powder dispersion;

[0070] (3) spray drying the carbon-titanium oxide powder dispersion, collecting the dried powder, and then sintering it at 750° C. for 3 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder;

[0071] (4) 10.0 g of hollow titanium oxide powder was added with 1.8 g of modified hydroxy fluorosilicone oil, 800 g of ethanol, and 0.1 g of tetrabutyl titanate. After stirring and refluxing at 80° C. for 4 h, the mixture was stirred at 110° C. for 3 h to complete the reaction and the excess solvent (ethanol) was removed to obtain a highly scattering and highly dispersible modified hollow titanium oxide.

[0072] The modified hydroxy fluorosilicone oil is prepared by the following process: 2.0 g of hydroxy fluorosilicone oil is mixed with 0.3 g of octyltriethoxysilane, 0.2 g of dibutyltin dilaurate is added, and the mixture is heated at 100° C. for 8 h to obtain the modified hydroxy fluorosilicone oil.

[0073] The particle size of the modified hollow titanium oxide prepared in Example 4 is 200-300 nm.

[0074] Embodiment 5:

[0075] (1) 0.10 g of nano-carbon powder with a particle size of 120 nm was added to 4000 g of ethanol and completely dispersed by ultrasonication; 5.5 g of hydroxypropyl cellulose was added and completely dissolved, and then stirred and cooled at 3° C., and then 150 g of tetrabutyl titanate was added and stirred and dispersed to obtain a mixed solution;

[0076] (2) 50 g of water and 300 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 3 ° C for 2 h, and then heated to 70 ° C and stirred for 5 h to obtain a gray carbon-titanium oxide powder dispersion;

[0077] (3) spray drying the carbon-titanium oxide powder dispersion, collecting the dried powder, and then sintering it at 750° C. for 3 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder;

[0078] (4) 10.0 g of hollow titanium oxide powder was added with 1.5 g of modified hydroxy fluorosilicone oil, 800 g of ethanol, and 0.1 g of tetrabutyl titanate. After stirring and refluxing at 80° C. for 4 h, the mixture was stirred at 110° C. for 3 h to complete the reaction and the excess solvent (ethanol) was removed to obtain a highly scattering and highly dispersible modified hollow titanium oxide.

[0079] The modified hydroxy fluorosilicone oil is prepared by the following process: 1.5 g of hydroxy fluorosilicone oil is mixed with 0.2 g of dimethyldiethoxysilane, 0.25 g of dibutyltin dilaurate is added, and the mixture is heated at 85° C. for 7.5 h to obtain the modified hydroxy fluorosilicone oil.

[0080] The particle size of the modified hollow titanium oxide prepared in Example 5 is 200-300 nm.

[0081] Comparative Example 1:

[0082] (1) 0.05 g of nano-carbon powder with a particle size of 150 nm was added to 1000 g of ethanol and completely dispersed by ultrasonication; 0.2 g of hydroxypropyl cellulose was added and dissolved completely, and then stirred at 4° C. to cool, and then 80 g of tetrabutyl titanate was added and stirred to obtain a mixed solution;

[0083] (2) 40 g of water and 400 g of ethanol were prepared into an ethanol-water solution, which was slowly poured into the above mixed solution, stirred at 5 ° C for 2 h, and then heated to 80 ° C and stirred for 4 h to obtain a gray carbon-titanium oxide powder dispersion;

[0084] (3) After the carbon-titanium oxide powder dispersion is spray-dried, the dried powder is collected and then sintered at 700° C. for 4 h to remove the carbon core, thereby obtaining a hollow titanium oxide powder.

[0085] 10 g of the hollow titanium oxide prepared in Comparative Example 1 and the modified hollow titanium oxide prepared in Example 1 were added to 100 mL of N,N-dimethylformamide to observe their dispersibility. The specific results are shown in Figure 3 As can be seen from the figure, the organic solvent dispersion prepared with the unmodified hollow titanium oxide powder in Comparative Example 1 almost completely precipitated after standing for 24 hours, while the modified powder dispersion in Example 1 only slightly precipitated after standing for 24 hours, indicating that the dispersibility of the modified titanium oxide is significantly improved.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing modified hollow titanium oxide, characterized in that: The following steps are involved: (1) preparing a mixed solution containing nano carbon powder, hydroxypropyl cellulose and tetrabutyl titanate; (2) adding ethanol aqueous solution, stirring at 0-5° C., and then heating to 70-90° C. and stirring to obtain a carbon-titanium oxide powder dispersion; (3) drying and sintering to remove the carbon core to obtain hollow titanium oxide powder; (4) reacting the hollow titanium oxide powder obtained in step (3) with modified hydroxy fluorosilicone oil and a catalyst in a solvent to obtain the modified hollow titanium oxide.

2. The preparation method according to claim 1, characterized in that: In step (1), the solvent of the mixed solution is ethanol; Preferably, the particle size of the nano carbon powder is 100 to 200 nm; Preferably, the mass ratio of the nano-carbon powder: ethanol: hydroxypropyl cellulose: tetrabutyl titanate is 1: 5000-50000: 4-100: 500-5000.

3. The preparation method according to claim 1, characterized in that: In step (2), the stirring time at 0-5°C is 1.5-3h; Preferably, the stirring time at 70-90° C. is 4-5 h.

4. The preparation method according to claim 1, characterized in that: In step (3), the sintering temperature is 700-800° C. and the sintering time is 1-4 hours; Preferably, the drying is spray drying.

5. The preparation method according to claim 1, characterized in that: In step (4), the reaction is stirred at 70-80° C. for 3-6 hours under reflux, and then stirred at 90-120° C. for 3-6 hours; Preferably, the solvent is ethanol; Preferably, the catalyst is tetrabutyl titanate, and the mass ratio of the catalyst to the hollow titanium oxide powder is 0.05-0.2:100; Preferably, the mass ratio of the modified hydroxy fluorosilicone oil to the hollow titanium oxide powder is 5 to 20:

100.

6. The preparation method according to claim 1, characterized in that: In step (4), the modified hydroxyfluorosilicone oil is hydroxyfluorosilicone oil modified by a silane coupling agent.

7. The preparation method according to claim 6, characterized in that: In step (4), the preparation method of the modified hydroxy fluorosilicone oil comprises the following steps: heating the hydroxy fluorosilicone oil, a silane coupling agent and an organic tin catalyst at 80 to 100° C. for 4 to 8 hours to obtain the modified hydroxy fluorosilicone oil; Preferably, the silane coupling agent is selected from at least one of octyltrimethoxysilane, methyltrimethoxysilane, octyltriethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane and dimethyldiethoxysilane.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the hydroxy fluorosilicone oil to the organotin catalyst is 1.5-2.5:0.15-0.25; Preferably, the mass ratio of the hydroxyfluorosilicone oil to the silane coupling agent is 5-20:0.1-5.

9. The modified hollow titanium oxide obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the modified hollow titanium oxide according to claim 9 in the preparation of cosmetics.

Citation Information

Patent Citations

  • Hollow titanium oxide high colour electrophoresis particle for electrophoresis display and preparation thereof

    CN101279233A

  • A hollow titanium oxide composite material, preparation method and application

    CN105406041B

  • A titanium dioxide@C hollow composite framework inlaid with precious metal silver, its preparation method and application

    CN113488651B

  • Hydroxyl fluorosilicone oil and preparation method thereof

    CN111848958A

  • Transparent easy-to-clean glass coating, preparation method thereof and transparent easy-to-clean glass

    CN113088110A